Relationship between universities and their stakeholders performed through the public private partnership - Sabolová, Veronika; Tetřevová, Liběna (University of Pardubice, 2012)
The aim of this paper is to provide theoretical evidence that the university and enterprise entity integration through the public private partnership is applicable and appropriate. This applicability and appropriateness will be judged by qualitative proofs based on characteristic features of all the participants and the public private partnership itself. This theoretical argumentation result will serve as a basis for empirical research on usability of the PPP principles in integration of universities and business entities in the Czech Republic.